2021
DOI: 10.1111/ans.16568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID‐19 pandemic first wave and public policy on elective and emergency surgery provision in Southern Queensland

Abstract: Background Several public health initiatives in Australia were implemented in March 2020 to contain the spread of COVID‐19. The effect of these initiatives on surgical provision is unknown. The primary objective was to determine the effect of public health policies and surgical society guidelines implemented during the pandemic on elective and emergency caseload of surgical specialities operating within South East Queensland. Methods This observational study utilized no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
4
12
0
Order By: Relevance
“…Emergency surgical workload during this time did not change, and our numbers in the pre‐COVID and COVID groups were similar (252 and 271 patients respectively). This is consistent with data from a recently published Queensland study 4 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Emergency surgical workload during this time did not change, and our numbers in the pre‐COVID and COVID groups were similar (252 and 271 patients respectively). This is consistent with data from a recently published Queensland study 4 …”
Section: Discussionsupporting
confidence: 93%
“…In the height of the COVID‐19 pandemic, Cairns Hospital introduced an acute surgical unit (ASU) in accordance with general surgeons Australia (GSA) 12‐point plan for emergency general surgery 2 . Additionally, a dedicated surgical rapid assessment unit (RAU) was created to improve emergency flow and redirect patients away from an overburdened emergency department 4 . The goal was to reduce overlap and redundancy in rostering, increase the availability of senior surgical staff and reduce emergency department workload and possible COVID‐19 exposure for surgical patients and staff.…”
Section: Introductionmentioning
confidence: 99%
“…Our audit demonstrated an overall reduction in surgical emergency admission of about 36%, while average age and gender distribution did not change significantly. Few Italian Authors have reported a much more significant reduction on the basis of their own local experience [6][7][8], while a study from Australia reported a minimal reduction in overall emergency cases of only 12%, and a subgroup analysis of the general surgery emergencies shows a variation of − 14% [9]. These disparities can be due to the different national guidelines, but the variations between the pre-Covid era and the first months of the Covid outbreak always present with a minus sign.…”
Section: Discussionmentioning
confidence: 99%
“…Our audit demonstrated an overall reduction in surgical emergency admission of about 36%, while average age and gender distribution did not change signi cantly. Few Italian Authors have reported a much more signi cant reduction on the basis of their own local experience [4][5][6], while a study from Australia reported a minimal reduction in overall emergency cases of only 12%, and a subgroup analysis of the general surgery emergencies shows a variation of -14% [7]. These disparities can be due to the different national guidelines, but the variations between the pre-Covid era and the rst months of the Covid outbreak always present with a minus sign.…”
Section: Discussionmentioning
confidence: 99%